Health professions students' attitudes and perceptions of interprofessional biases. (26th March 2019) - Gillette, Chris; Dinkins, Melissa M; Bliss, Rebecca; Pfaff, Michele; Maupin, Elizabeth; Badran, Aseel; Manolakis, Michael; Smith, Lisa; Sweetman, Melissa
Abstract: Objective: The purpose of this study was to examine attitudes toward interprofessional, team-based care in first-year health professions students. Methods: A cross-sectional questionnaire was administered to all first-year health professions students in their first semester at one university using the Interprofessional Attitudes Scale (IPAS). Kruskal–Wallis tests were used to analyze the data. Key findings: Results indicated only two significant differences among students in IPAS subdomains: teamwork (χ 2 = 13.11, df = 3, P = 0.004) and patient-centredness (χ 2 = 40.75, df = 3, P < 0.0001). Conclusions: Not all health professions students come into their formal education with the same level of attitudes toward team-based care. Educators should consider this when designing IPE activities.